Need for social work education and practice in the prevention of HIV/AIDS: A case study of Pakistan. Issue 1 (2nd January 2017) - Naqvi, Raazia Hassan; Ibrar, Muhammad
ABSTRACT: HIV/AIDS in Pakistan was first diagnosed in 1986. The National AIDS Control Program was formulated in 1987. Unfortunately, after spending 26 years on the prevention of HIV/AIDS, we are still missing a major professional field in this effort: there is no evidence of the social worker in the National Health Policy of 2001 and in the National HIV/AIDS Policy of 2007. The aim of this study is to present the history and analysis of AIDS policies, laws, and strategic framework of Pakistan and make suggestions in social work education and practice's role in combating HIV/AIDS in the country.